Molecular detection of some virulence genes for Proteus mirabilis bacteria isolated from diabetic foot ulcers (Eurasian Medical Research Periodical, 2022)
Molecular analysis was used in this investigation to identify the bacterium Proteus mirabilis, which was collected from individuals with diabetic foot ulcers. Two hundred fifty wound swab samples were obtained from diabetic patients receiving treatment at Al-Diwaniyah Teaching Hospital and patients receiving treatment at private clinics between October 2021 and February 2022. According to the findings, eighty (80) positive isolates were found by the bacteriological test, biochemical tests, and VITEK2 system. PCR was performed using a specific primer (16SrRNA) to identify the genus Proteus and distinguish it from the other Enterobacteria and bacteria. PCR methods were utilized in order to investigate the genes ureR, which is accountable for the production of the enzyme urease; hpmA, which is accountable for the production of hemolycin; zapA, which is accountable for the production of the protease enzyme; and flaA, which is accountable for the production of flagella. These genes showed up with relative frequencies of 68.75 percent, fifty percent, one hundred percent, and one hundred percent. The PCR technology does the sequence analysis of the Nitrogen bases on the samples used in this investigation demonstrates a level of consistency in strains of P. mirabilis of the WHO that reached up to 98 percent. This study demonstrated a high level of sensitivity and specificity of P. mirabilis diagnosis with the PCR technology, which is less expensive and more efficient than the conventional approaches currently utilized in medical facilities and research laboratories.